Building MedVenture – A mobile health application to improve adolescent medication adherence – Using a multidisciplinary approach and academic–industry collaboration. (May 2021) - Mehta, Pooja; Moore, Susan L; Bull, Sheana; Kwan, Bethany M
Objective: Mobile health (mHealth) tools are increasingly used to support medication adherence yet few have been designed specifically for the pediatric population. This paper describes the development of a medication adherence application ( MedVenture ) using the integration of patient and healthcare provider input, health behavior theory, and user engagement strategies for adolescents with chronic gastrointestinal disease. Methods: MedVenture was created by a multidisciplinary research team consisting of a gastroenterologist, a social health psychologist, software developers, and digital health researchers. Healthcare providers and adolescent patients were interviewed to identify barriers to medication adherence, explore ways that technologies could best support medication adherence for both patients and providers, and determine user requirements and core design features for a digital health tool. Intervention mapping was used to match themes from qualitative content analysis to known efficacious adherence strategies, according to a conceptual framework based on self-determination theory. Iterative design with review by the research team and two rounds of user testing informed the final prototype. Results: Three themes were identified from content analysis: 1) lack of routine contributes to nonadherence, 2) adolescents sometimes purposefully forgo medications, and 3) healthcare providers would prefer a tool that promotes patient self-management rather than one that involves patient-provider interaction. These findings, combined with evidence-based adherence and user engagement strategies, resulted in the development of MedVenture – a game-based application to improve planning and habit formation. Conclusions: Academic-industry collaboration incorporating stakeholders can facilitate the development of mobile health tools designed specifically for adolescents with chronic disease.